Pemanfaatan laman BIPA daring sebagai media pembelajaran BIPA berkonteks kearifan lokal di ASEAN - Syukron Ramadloni; Liliana Muliastuti; Miftahulkhairah Anwar (Badan Pengembangan dan Pembinaan Bahasa, 2022)
Associated with the context of local wisdom, BIPA Daring as a learning media and reference for network-based BIPA activities has not been discussed in scientific article. Local wisdom is used as anticipation of BIPA learners in terms of culture shock and as a lure to attract BIPA learners. Unfortunately, the most local wisdom displayed in BIPA teaching materials raises Javanese culture only. Meanwhile, Indonesia's local wisdom is very diverse. This study aims to describe how to utilize Indonesian local wisdom material in the BIPA Daring and how to utilize it in scope of the ASEAN region. This research method uses qualitative descriptive analysis conducted in February 2022 at Pustanda. Data sources obtain from the website administrator and three BIPA teachers. Data collection techniques by direct observation and obtained by purposive sampling. Data validation is done by triangulating data sources. The results showed that BIPA Daring provides materials related to Indonesian local wisdom in two channels. The conclusion is that BIPA Daring contained the local wisdom of the Indonesian people tucked into each teaching material and the high interest of service users in the ASEAN region regarding Indonesian local wisdom